Maximum Production from the Tropical Dry Deciduous Forests - Sagreiya, K. P.; Nath, B. (Indian Forester, 1968)
The Coppice with Reserves system has now been applied to the dry deciduous forests of M.P. and to a certain extent to similar forests in other States, for the last over 30 years. While intrinsically the results have been extremely satisfactory, in that wherever the crops were properly protected and tended, the value of the reserves increased by leaps and bounds, the site-quality improved and regeneration of the principal species was induced. But wherever the valuable pole crop was cashed prematurely and the forests were not protected against fires and heavy grazing the crop regressed. The working of the forests mostly in the interest of the coppice (as most forests had too much malformed growth) on a rotation of 30-40 years also led to removal of much of the reserves. A plea is now made to work the forests more in the interest of the reserves which now predominate, as was the case with coppice in the first round of working, on a cutting cycle of 10 to 15 years, with periodic inventories with a view to maximise production. Biolley's Methode du controle should serve as a guide. It is suggested that the State Forest Research Institute, Jabalpur, M.P., should lay out plots to determine the optimum growing stock to get the highest production.